Research on Germination and Emergence Performance Enhancing Treatments on Sage (Salvia spp.) Species - Çiğdem Sönmez; Adem Gökçöl; Ayşe Özge Şimşek Soysal; Emine Bayram; Ahmet Esen Çelen (Turkish Journal of Agriculture: Food Science and Technology)
In this study, Common Sage (Salvia officinalis L.) and Anatolian Sage (Salvia fruticosa Mill.) seeds, which are important medicinal plants, were used as plant material. The seeds of the Salvia genus have dormancy as they have seed husks containing a mucilaginous layer. For this reason, in order to improve the germination and emergence performance of seeds and to increase the quality of seeds, nine pre-sowing treatments (KNO3 application, GA3 application, polymer coating, polymer coating + KNO3, polymer coating + GA3, priming, priming + polymer coating, priming + polymer coating + KNO3, priming + polymer coating + GA3) were applied to the seeds and the effect of applications on germination rate, emergency rate, germination speed and emergency speed were investigated.